Behavioral evidence for a differential modulation of semantic processing and lexical production by aging: a full linear mixed-effects modeling approach. Issue 1 (2nd January 2018) - Boudiaf, Naïla; Laboissière, Rafael; Cousin, Émilie; Fournet, Nathalie; Krainik, Alexandre; Baciu, Monica
ABSTRACT: The effect of normal aging on lexical production and semantic processing was evaluated in 72 healthy participants. Four tasks were used, picture naming (PN), picture categorization (PC), numerical judgment (NJ), and color judgment (CJ). The dependence of reaction time (RT) and correct responses with age was accounted by mixed-effects models. Participants underwent neuropsychological testing for verbal, executive, and memory functions. The RTs increase significantly with age for all tasks. After parceling out the non-specific cognitive decline, as reflected by the NJ task, the RT for the PN task decreases with age. Behavioral data were interpreted in relation with neuropsychological scores. Our results suggest that (a) naming becomes more automatic and semantic processing slightly more difficult with age, and (b) a non-specific general slowdown of cognitive processing occurs with age. Lexical production remained unaltered, based on compensatory automatic processes. This study also suggests a possible slowdown of semantic processing, even in normal aging.